83.7k views
1 vote
Explain ?............

Explain ?............-example-1
User Hvester
by
5.4k points

2 Answers

4 votes

Hello from MrBillDoesMath!

Answer:

128b - 59


Discussion:

-11 + 16 (8b - 3) =

-11 + (16((8)b + 16(-3) = => as 16*8 = 128 and (16)(-3) = -48

-11 + 128b -48 = => as 48 + 11 = 59

128b - 59


Thank you,

MrB

User Felix Livni
by
5.4k points
2 votes

Answer:

128b - 59

Explanation:

-11 + 16 (8b-3)

Distribute the 16

-11 +16*8b +16 (-3)

-11+ 128b -48

Combine like terms

128b - 59


User TomVW
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.